Conceptions of transformation in adult education: Views of self, society, and social change. - unknown unknown (Adult Education Research Conference, 1993)
The purpose of this symposium is to identify and critically examine theoretical assumptions implicit in four views of transformative adult education, with particular emphasis on notions of self, society, social change, and the role of the adult educator in transformation.